Go-Food dan Gaya Hidup Konsumtif Mahasiswa IAIN Surakarta - Siti Ulil Hidayati Walaf Doliyah (Universitas Islam Negeri Raden Mas Said Surakarta, 2018)
The research aims to determine the impact of the Go-Food platform on the consumptive lifestyle among students. With a qualitative approach, the study tried to identify how Go-Food facilitates a variety of student needs, especially for students who have a consumptive lifestyle. The interview was conducted against 12 students who routinely use Go-Food to buy food. To enrich the discussion, theoretical studies are also conducted. The results showed that Go-Food presence can facilitate a variety of student needs, but not to the extent of excessive consumptive.Keywords: consumtif, Go-Food, students